ETNOMATEMATIKA PERMAINAN TRADISIONAL: PERMAINAN LOMPAT TALI SEBAGAI MEDIA BELAJAR MATEMATIKA KELAS 3 MI NAHDLATUTH THULLAAB GEDANGSARI - Ita Nasyithotun Nafisah; Suratiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of an ethnomathematics approach through the traditional jump rope game as a learning medium in teaching length measurement to third-grade students of MI Nahdlatuth Thullaab Gedangsari. The background of this study is based on students’ low ability to understand mathematical concepts contextually, as well as the tendency of learning processes that are still teacher-centered, combined with the use of learning resources that are less relevant to students’ daily lives. This research employed a qualitative approach with a descriptive method, using observation and interviews with teachers and students as data collection techniques. The results show that the implementation of the ethnomathematics approach through the jump rope game successfully increased students’ engagement and enthusiasm in learning mathematics. Students became more active, were able to understand the concept of length measurement using both standard and non-standard units and could relate the material to their daily experiences. Based on the assessment results, 14 students achieved a high category, 11 students were in the moderate category, and none were in the low category, indicating a very high level of learning achievement. Therefore, it can be concluded that the use of the traditional jump rope game within an ethnomathematics approach is effective as a contextual, enjoyable, and meaningful learning medium, while also contributing to the preservation of local culture. Keywords: ethnomathematics, jump rope game, mathematics learning